Bruch's membrane and Brücke's muscle in the pars plana region: original article - Jonas, Jost B.; Jonas, Rahul A.; Jonas, Shefali B.; Panda-Jonas, Songhomitra (Acta ophthalmologica, 2024)
Purpose: To examine Bruch's membrane (BM) in association with the longitudinal part of the ciliary muscle (LPCM) in the pars plana region. Methods Using light microscopy, we histomorphometrically assessed BM and the LPCM in the pars plana region. Results The histomorphometric study included 51 eyes (51 patients; mean age: 60.8 ± 15.0 years; axial length: 26.0 ± 3.3 mm; range: 21.0-36.0 mm). The LPCM (total length: 4.60 ± 1.10 mm) ended 1.15 ± 0.56 mm anterior to the ora serrata. Within the pars plana region, the LPCM (length: 2.58 ± 0.98 mm) had direct contact with BM for 1.95 ± 0.99 mm (71.1 ± 18.4% of the BM undersurface), while a capillary layer was interposed between the BM and the LPCM for 0.70 ± 0.40 mm (29.0 ± 18.4%). In the pars plana region free of LPCM close to the ora serrata, the percentage of BM covered by the capillary layer was higher than in the pars plana region containing the LPCM (63.0 ± 42.1% vs. 29.0 ± 18.4%; p < 0.001). At the LPCM end, BM was in direct contact with a collagenous tissue from the LPCM and was focally thickened as compared to BM with an underlying capillary layer (9.5 ± 5.3 μm vs. 4.3 ± 1.2 μm; p < 0.001). Conclusions The direct contact of BM with the LPCM in the pars plana in association with focal BM thickening at the LPCM end suggests an insertion of LPCM on the BM. Taking into account the biomechanical strength of BM, it may imply a functional unit of the LPCM with BM in the process of accommodation with a secondary movement of the posterior BM and tertiary thickening of the subfoveal choroidal space.